Coalescence and noncoalescence of sessile drops: Impact of surface forces - Karpitschka, Stefan; Hanske, Christoph; Fery, Andreas; Riegler, Hans (Langmuir, 2014)
Due to capillarity, sessile droplets of identical liquids will instantaneously fuse when they come in contact at their three-phase lines. However, with drops of different, completely miscible liquids, instantaneous coalescence can be suppressed. Instead, the drops remain in a state of noncoalescence for some time, with the two drop bodies connected only by a thin neck. The reason for this noncoalescence is the surface tension difference, Δγ, between the liquids. If Δγ is sufficiently large, then it induces a sufficiently strong Marangoni flow, which keeps the main drop bodies temporarily separated. Studies with spreading drops have revealed that the boundary between instantaneous coalescence and noncoalescence is sharp (Karpitschka, S.; Riegler, H. J. Fluid. Mech. 2014, 743, R1). The boundary is a function of two parameters only: Δγ and ⊖a, the arithmetic mean of the contact angles in the moment of drop-drop contact. It appears plausible that surface forces (the disjoining pressure) could also influence the coalescence behavior. However, in experiments with spreading drops, surface forces always promote coalescence and their influence might be obscured. Therefore, we present here coalescence experiments with partially wetting liquids and compare the results to the spreading case. We adjust different equilibrium contact angles (i.e., different surface forces) with different substrate surface coatings. As for spreading drops, we observe a sharp boundary between regimes of coalescence and noncoalescence. The boundary follows the same power law relation for both partially and completely wetting cases. Therefore, we conclude that surface forces have no significant, explicit influence on the coalescence behavior of sessile drops from different miscible liquids. © 2014 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-20